Struktur Teks Wacana Model Teun A. Van Dijk pada Pemberitaan Program Makan Bergizi Gratis (MBG) dalam Media Online CNN Indonesia, Tempo.co, dan Detikcom - Zulmi Zul Zakiyah; Rina Andriani; Desma Yuliadi Saputra (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to analyze the text structure of news coverage on the Free Nutritious Meals (MBG) Program published by the online media outlets CNN Indonesia, Tempo.co, and Detikcom using Teun A. Van Dijk's discourse analysis model. This study employed a descriptive qualitative approach by analyzing the macrostructure, superstructure, and microstructure of the news texts. The findings indicate that all three media outlets focus on the same theme, namely President Prabowo Subianto's response to the rejection of the MBG Program, but differ in the way they construct the news. CNN Indonesia emphasizes the urgency of the MBG Program as a solution to food security issues, Tempo.co highlights the social dynamics and the program's objective of supporting disadvantaged communities, while Detikcom emphasizes the President's defense of the MBG Program as a priority public policy. These findings indicate that each media outlet employs different strategies in presenting information according to its editorial characteristics.